α-Ketoglutarate stimulates cell growth through the improvement of glucose and glutamine metabolism in C2C12 cell culture - Yang, Bingquan; Liu, Yuefei; Steinacker, Jürgen Michael (Frontiers in Nutrition, 2023)
Introduction: Cellular adaptation to physical training and energy metabolism play important role during physical exercise. This study sought to investigate the effects of α-KG on cell growth and energy metabolism in C2C12 cell culture. Methods: C2C12 cells were cultured in media pretreated without (control) or with α-KG at different concentrations, and cells and media were harvested every 24 h for eight days. From cell counts, specific cell growth rate (SGR) and doubling time were calculated. The content of glucose, glutamate, lactate and ammonia in media was determined and specific consumption rate (SCR) or production rate (SPR) was calculated. Additionally, cell colony formation efficiency (CFE) was determined. Results: The control cells showed a CFE at 50%, and a typical cell growth curve in the first 5 days with a mean SGR at 0.86/day and a mean cell count doubling time at 19.4 hours. In the group with α-KG at 100 mM, the cells underwent rapid cell death and thus no further analysis. The treatment with α-KG at lower concentration (0.1 mM and 1.0 mM) led to a higher CFE at 68% and 55%, respectively, whereas those in groups with higher α-KG concentration decreased (10% and 6% for 20mM and 30 mM α-KG, respectively). The mean SGR was 0.95/day, 0.94/d, 0.77/day, 0.71/day and 0.65/day for groups treated with α-KG at 0.1, 1.0, 10.0, 20.0 and 30.0 mM, respectively), the corresponding cell count doubling time was 19.4, 17.6,17.8, 20.9, 24.6 and 24.7 hours, respectively. In comparison with that of control group, the mean glucose SCR decreased in all the groups treated with α-KG, while the mean glutarate SCR remained unchanged; the mean lactate SPR increased in the groups treated with α-KG ≥ 20.0 mM. Finally, the mean SPR of ammonia was lower in all α-KG groups than that in control. Discussion and conclusion: The treatment with α-KG at lower concentration increased cell growth while at higher concentration decreased, and α-KG reduced glucose consumption and ammonia production. Therefore, α-KG stimulates cell growth in a dose-dependent manner, which is likely through improvement of glucose and glutamate metabolism in a C2C12 culture setting.